2011
DOI: 10.1002/hed.21713
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting salivary miR‐31 as a clinical biomarker of oral squamous cell carcinoma

Abstract: Our results point to a potential application of salivary miR-31 as a biomarker for early detection and postoperative follow-up of oral carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(200 citation statements)
references
References 28 publications
5
182
1
3
Order By: Relevance
“…64,128 Moreover, plasma miRNAs are shown to be reduced after tumor resection, implying that they may be released from cancerous tissues into circulation and hence is a potential marker for disease progression. 62,64 This was seen in case of plasma and salivary miR-31 47 and plasma miR-184. 62 …”
Section: Mirnas As Predictive Biomarkers In Oral Carcinomamentioning
confidence: 81%
“…64,128 Moreover, plasma miRNAs are shown to be reduced after tumor resection, implying that they may be released from cancerous tissues into circulation and hence is a potential marker for disease progression. 62,64 This was seen in case of plasma and salivary miR-31 47 and plasma miR-184. 62 …”
Section: Mirnas As Predictive Biomarkers In Oral Carcinomamentioning
confidence: 81%
“…Park and others 6 found two miRNAs (miR-125a and miR-200a) that had significantly reduced levels in the saliva of oral cancer patients compared to controls and found that these two markers could be used for detecting OSCC. Liu and others 30 recently discovered that salivary miRNA-31 (miR-31) was significantly elevated in patients with oral cancer at all stages of disease and tumor size. This study also determined that salivary miR-31 was more abundant than blood miR-31, indicating oral tumor origin of this biomarker.…”
Section: Salivary Transcriptomementioning
confidence: 99%
“…The most accessible of these in HNSCC patients are plasma and saliva. Several studies have focused on miRNA profiling saliva of oral cavity tumour patients in the search for a diagnostic tool, with promising results [70,71]. Liu and colleagues compared miRNA detection in both plasma and saliva in oral cavity tumours, finding expression levels to be higher in saliva [70].…”
Section: Detection Of Micrornas In Body Fluidsmentioning
confidence: 99%
“…Several studies have focused on miRNA profiling saliva of oral cavity tumour patients in the search for a diagnostic tool, with promising results [70,71]. Liu and colleagues compared miRNA detection in both plasma and saliva in oral cavity tumours, finding expression levels to be higher in saliva [70]. The non-invasive collection of body fluids such as saliva for measurement of miRNA expression will provide a useful avenue for miRNA profiling, and diagnostic or prognostic tool development, in the future.…”
Section: Detection Of Micrornas In Body Fluidsmentioning
confidence: 99%
See 1 more Smart Citation